2021
DOI: 10.1097/sga.0000000000000589
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Transnasal Endoscopy to a Scottish District General Hospital

Abstract: Esophagogastroduodenoscopy can be uncomfortable and distressing with many patients opting for conscious sedation over topical local anesthetic spray. Transnasal endoscopy is an alternative and we sought to assess how easily it could be introduced to a district general hospital and how acceptable patients found it. Selected patients requiring diagnostic endoscopy were offered transnasal endoscopy with topical nasal anesthetic by clinicians new to transnasal endoscopy but competent at esophagogastroduodenoscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Data available from two endoscope manufacturers (Fujifilm and Olympus) suggest an upward trend in uTNE sales over the past year (2020-2021) and it will be important to ascertain if this increase is also replicated in the number of procedures performed. Furthermore, regional case studies [65,66] have shown that uTNE can easily be adopted by UK clinicians experienced in cEGD and that it is well tolerated by patients. In the absence of formal guidelines, such studies may prove to be influential in providing a blueprint for other UK centers considering uTNE.…”
Section: Current Status Of Utne In the Ukmentioning
confidence: 99%
“…Data available from two endoscope manufacturers (Fujifilm and Olympus) suggest an upward trend in uTNE sales over the past year (2020-2021) and it will be important to ascertain if this increase is also replicated in the number of procedures performed. Furthermore, regional case studies [65,66] have shown that uTNE can easily be adopted by UK clinicians experienced in cEGD and that it is well tolerated by patients. In the absence of formal guidelines, such studies may prove to be influential in providing a blueprint for other UK centers considering uTNE.…”
Section: Current Status Of Utne In the Ukmentioning
confidence: 99%